Gene expression and plant performance in oryzacystatin-I expressing transformed tobacco (Nicotiana tabacum L. cv Samsun) plants under abiotic stress - Kunert, Karl J. (University of Pretoria, 2013)
Thesis (PhD (Botany))--University of Pretoria, 2006.